iPSC line DHMCi019-A is generated from a patient with hereditary nephrotic syndrome harboring compound heterozygous NPHS2 variants - Tabatabaeifar, Mansoureh; Matthes, Robert; Burau, Karin; Schaefer, Franz; Jung-Klawitter, Sabine (Stem cell research, 2025)
Mutations in NPHS2, encoding the slit diaphragm protein podocin, are a common cause of steroid-resistant nephrotic syndrome in children. Over 120 mutations have been identified, leading to diverse subcellular podocin localization patterns. Peripheral blood mononuclear cells (PBMCs) were obtained from a five-year-old female patient carrying a compound-heterozygous NPHS2 mutation (c.379G>A(;)c.857_858del). Patient-derived induced pluripotent stem cells (iPSCs) were generated using the Cytotune®-iPSC 2.0 Sendai Reprogramming Kit (Invitrogen). These iPSCs exhibited normal karyotype and morphology, with confirmed expression of undifferentiated hPSC state markers and differentiation potential into all three germ layers.
Gesehen am 16.01.2026